Collared versus collarless hydroxyapatite-coated stems for primary cementless total hip arthroplasty; a systematic review of comparative studies. Is there any difference in survival, functional, and radiographic outcomes? - Giovanoulis Vasileios; Kenanidis Eustathios; Aïm Florence; Gamie Zakareya; Marmor Simon; Potoupnis Michael; Lustig Sébastien; Tsiridis Eleftherios (SICOT-J, 2024)
Introduction: This systematic review aims to critically assess the literature comparative studies investigating collared and collarless Corail stem in primary total hip arthroplasty (THA) to find differences in revision rates, radiographic and clinical outcomes, and postoperative complications between these two types of the same stem. Methods: Eligible studies were found by searching PubMed, Science Direct/Scopus, and the Cochrane Database of Systematic Reviews from conception till May 2023. The PRISMA guidelines were followed. The investigation encompassed randomized controlled trials, case series, comparative, cohort, and observational studies that assessed at least one comparative outcome or complication between collared and collarless Corail stems. Results: Twelve comparative studies with 90,626 patients undergoing primary THA were included. There were 40,441 collared and 58,543 collarless stems. The follow-up ranged from 12 to 360 months. Our study demonstrated no significant difference in stem revision relative risk (RR = 0.68; 95% confidence interval (CI), 0.23, 2.02; p = 0.49), number of radiolucent lines (RR = 0.3; 95% CI, 0.06, 2.28; p = 0.29) and overall complication risk (RR = 0.62; 95% CI, 0.22, 1.76; p = 0.37) between collared and collarless stems. The collared stems demonstrated significantly lesser subsidence (mean difference: 1.01 mm; 95% CI, −1.77, −0.25; p = 0.009) and risk of periprosthetic fractures (RR = 0.52; 95% CI, 0.29, 0.92; p = 0.03). Conclusion: The comparative studies between collared and collarless stem groups showed similar survival and overall complication rates and functional outcomes. The similar revision rates between groups make the impact of higher subsidence for collarless stems uncertain. The lower risk of periprosthetic fractures in the collared stems group must be clarified further but could be related to increased rotational stability.